Jupiter's stratospheric hydrocarbons and temperatures after the July 2009 impact from VLT infrared spectroscopy - Fletcher, L; Orton, G; de Pater, I; Mousis, O (2010)
Aims. Thermal infrared imaging and spectroscopy of the July 19, 2009 Jupiter impact site has been used to identify unique features of the physical and chemical atmospheric response to this unexpected collision. Methods. Images and high-resolution spectra of methane, ethane and acetylene emission (7-13 μm) from the 2009 impact site were obtained by the Very Large Telescope (VLT) mid-infrared camera/spectrometer instrument, VISIR. An optimal estimation retrieval algorithm was used to determine the atmospheric temperatures and hydrocarbon distribution in the month following the impact. Results. Ethane spectra at 12.25 μm could not be explained by a rise in temperature alone. Ethane was enhanced by 1.7-3.2 times the background abundance on July 26, implying production as the result of shock chemistry in a high C/O ratio environment, favouring an asteroidal origin for the 2009 impactor. Small enhancements in acetylene emission were also observed over the impact site. However, no excess methane emission was found over the impact longitude, either with broadband 7.9-μm imaging 21 h after the impact, or with center-to-limb scans of strong and weak methane lines between 7.9 and 8.1 μm in the ensuing days, indicating either extremely rapid cooling in the initial stages, or an absence of heating in the upper stratosphere (p < 10 mbar) due to the near-horizontal orientation of the impact. Models of 12.3-μm spectra are consistent with a â‰̂ 3 K rise in the lower stratosphere (p > 10 mbar), though this solution is highly dependent on the spectral properties of stratospheric debris. The enhanced ethane emission was localised over the impact streak, and was diluted in the ensuing weeks by redistribution of heated gases by zonal flow and mixing with the unperturbed jovian air. Conclusions. The different thermal energy deposition profiles, in addition to the highly reducing (C/O > 1) environment and shallow impactor angle, suggest that (a) the 2009 plume and shock-fronts did not reach the sub-microbar altitudes of the Shoemaker-Levy 9 plumes; and (b) models of a cometary impact are not directly applicable to the unique impact circumstances of July 2009. © 2010 ESO.